2016
DOI: 10.1073/pnas.1609057113
|View full text |Cite
|
Sign up to set email alerts
|

Defective HIV-1 proviruses produce novel protein-coding RNA species in HIV-infected patients on combination antiretroviral therapy

Abstract: Despite years of plasma HIV-RNA levels <40 copies per milliliter during combination antiretroviral therapy (cART), the majority of HIV-infected patients exhibit persistent seropositivity to HIV-1 and evidence of immune activation. These patients also show persistence of proviruses of HIV-1 in circulating peripheral blood mononuclear cells. Many of these proviruses have been characterized as defective and thus thought to contribute little to HIV-1 pathogenesis. By combining 5′LTR-to-3′LTR single-genome ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
330
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(369 citation statements)
references
References 40 publications
34
330
0
5
Order By: Relevance
“…QVOAs rely on limiting dilutions of replicates of stimulated CD4 + T cells to calculate maximal likelihood estimates of infectious units per million cells (IUPM) (2,23,28). Furthermore, QVOAs strictly measure replication-competent virus, while HIV DNA, p24 antigen, or viral RNA assays may be confounded by the presence of defective proviruses (29,30). Upon treating ex vivo CD4 + T cells with combinations of CD8 + T cells and LRAs, we observed consistent reductions in levels of HIV DNA that, surprisingly, were not accompanied by reductions in infectious viral reservoirs as mea- Figure 2, A and C).…”
Section: Resultsmentioning
confidence: 99%
“…QVOAs rely on limiting dilutions of replicates of stimulated CD4 + T cells to calculate maximal likelihood estimates of infectious units per million cells (IUPM) (2,23,28). Furthermore, QVOAs strictly measure replication-competent virus, while HIV DNA, p24 antigen, or viral RNA assays may be confounded by the presence of defective proviruses (29,30). Upon treating ex vivo CD4 + T cells with combinations of CD8 + T cells and LRAs, we observed consistent reductions in levels of HIV DNA that, surprisingly, were not accompanied by reductions in infectious viral reservoirs as mea- Figure 2, A and C).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we report optimized methods that enable sensitive and rapid detection of subfemtomolar cell-associated HIV gag p24 protein in HIV-infected CD4 + T cells from ART-suppressed individuals. Quantifying very small amounts of cell-associated viral antigen produced by low numbers of cells from aviremic/low-reservoir HIV + individuals is an important advancement, as viral protein expression is believed to contribute to tissue inflammation and persistent immune activation, and induction is a prerequisite for several investigational immune-mediated "kill" strategies (3)(4)(5)40). The assay can be completed in approximately 1 hour, typically requires 1-2 million peripheral CD4 + T cells from ART-suppressed HIV + individuals, and can be applied to quantify viral protein in cell lysates or culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Although a positive trend was observed, this did not reach statistical significance, which may be attributable, in part, to poor PCR probe recognition due to mismatches in HIV proviral sequences or to the inability of inducible RNA to make protein. Conversely, the presence of transcriptionally competent "defective" proviruses capable of producing aberrant gag protein that may be poorly recognized by the p24 antibody is also a possible explanation (40). Worth noting, significant correlations were observed between HDACi-induced cell-associated RNA and protein from blood CD4 + T cells in subjects treated clinically with HDAC inhibitors, and further work is ongoing to inform on the correlations between p24 immunoassay and other viral endpoints, including qVOA.…”
Section: Discussionmentioning
confidence: 99%
“…Initial evidence for this route of persistence came from the independent detection of multiple proviruses with exactly the same viral sequence or integration site within host cells (2)(3)(4)(5)(6). Full genome sequencing studies have established that most proviruses present in resting CD4 + T cells are defective (6)(7)(8), and thus many of these proviruses are unlikely part of the latent reservoir. Nevertheless, recent work from several groups has demonstrated that cells carrying replication-competent proviruses can also clonally expand in vivo (9-12).…”
mentioning
confidence: 99%